The modulation of conditional assertions and its effects on reasoning - Quelhas, Ana Cristina (2012)
The theory of mental models postulates that conditionals of the sort, if A then C, have a “core” meaning referring to three possibilities: A and C, not-A and C, and not-A and not-C. The meaning of a conditional’s clauses and general knowledge can modulate this meaning, blocking certain possibilities or adding relations between the clauses. Four experiments investigated such interpretations in factual and deontic domains. In Experiment 1, the participants constructed instances of what was possible and what was impossible according to various conditionals. The results corroborated the general predictions of the model theory and also the occurrence of modulation. The resulting interpretations governed the conclusions that participants accepted in Experiment 2, which also yielded the predicted effects of a time limit on responding. In Experiment 3, the participants drew the predicted conclusions for themselves. In Experiment 4, modulation led to predicted temporal relations between A and C. We relate these results to current theories of conditionals.